2020
DOI: 10.3390/ijms21134634
|View full text |Cite
|
Sign up to set email alerts
|

New Insight into the Composition of Wheat Seed Microbiota

Abstract: Endophytes are associated with host plants throughout their life history from seed germination to fruit development. One of the most important plant organs colonized by endophytic microbiota is the seed. The aim of this study was to determine the structure of the seed core microbiome inhabiting the endosperms and embryos of eight wheat cultivars with the use of a culture-independent technique. The seeds of Triticum aestivum L. cv. Hondia, Wilejka, STH, Opcja, Tybalt, Euforia and Triticum spelta L. cv. Rokosz a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 47 publications
(98 reference statements)
5
33
0
Order By: Relevance
“…Among the most representative genera, Cutibacterium has been identified, which is widely known as a commensal and is part of the human skin microbiota. However, a recent study, in support of our data, demonstrated the presence of Cutibacterium as an endophyte of roots and leaves in the wheat cultivars Triticum spelta cv Rokosz and Triticum aestivum cv Hondia ( Kuźniar et al, 2020 ). It is also very interesting, as reported by Shaffer et al (2018) , that this genus has been classified as a hyphal endosymbiont of a leaf fungal endophyte ( Fusarium concolor ) from Hybanthus prunifolius .…”
Section: Discussionsupporting
confidence: 89%
“…Among the most representative genera, Cutibacterium has been identified, which is widely known as a commensal and is part of the human skin microbiota. However, a recent study, in support of our data, demonstrated the presence of Cutibacterium as an endophyte of roots and leaves in the wheat cultivars Triticum spelta cv Rokosz and Triticum aestivum cv Hondia ( Kuźniar et al, 2020 ). It is also very interesting, as reported by Shaffer et al (2018) , that this genus has been classified as a hyphal endosymbiont of a leaf fungal endophyte ( Fusarium concolor ) from Hybanthus prunifolius .…”
Section: Discussionsupporting
confidence: 89%
“…However, recent studies endorse more the idea of an interkingdom exchange of microbes during plant domestication than the possibility of contamination. For example, Kuźniar and colleagues [73] studied eight wheat seeds microbiota in different compartments of seed (the embryo, endosperm, and the seed coat) and they found Cutibacterium in all the parts of the studied cultivars. Many other recent studies also found Propionibacterium as a member of the core microbiota of cereal seeds such as wheat, barley, maize and rice [20] , [73] , [74] , [75] .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kuźniar and colleagues [73] studied eight wheat seeds microbiota in different compartments of seed (the embryo, endosperm, and the seed coat) and they found Cutibacterium in all the parts of the studied cultivars. Many other recent studies also found Propionibacterium as a member of the core microbiota of cereal seeds such as wheat, barley, maize and rice [20] , [73] , [74] , [75] . Interestingly, Campisano and colleagues [76] found a subspecies of Propionibacterium acnes in grapevine ( Vitis vinifera L.), which evolved from the human-associated strain since a time comparable with the beginning of grapevine domestication.…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirmed that the microbiome of wheat grains depends on the wheat variety; the same trend was reported by Safin et al [ 66 ] and Comby et al [ 67 ]. Furthermore, Kuzniar et al [ 68 ] found that the seed-borne microbiome was not statistically significantly dependent on the wheat cultivars. Importantly, the seed-associated microbiotas, which are expected to be transferred vertically, have the potential to coadapt with their host over generations to different harsh environments [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding endophytes inhabiting spring wheat grains are equally scarce. It is worth emphasizing that grain endophytes are highly interesting due to their ability to be transmitted vertically between generations [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. A better understanding and manipulation of endophytes are considered novel promising strategies to mitigate the adverse impacts of global climate change on agricultural production and to improve the nutritional quality of plant-based foods.…”
Section: Introductionmentioning
confidence: 99%